Attention Deficit Hyperactivity Disorder in Children and Adolescents 2013
DOI: 10.5772/53865
|View full text |Cite
|
Sign up to set email alerts
|

Neurodevelopmental Pathways of Childhood ADHD into Adulthood: Maturational Lag, Deviation, or Both?

Abstract: The DSM-[ ], which should be published in , will in all likelihood have a category named Neurodevelopmental Disorders, under which "DHD will resort. This shift in nosology lays the foundation of the argument that will be put forward in this chapter, therefore the following points need to be emphasised and warrants further discussion. Firstly, this categorisation is based on shared aetiology, rather than shared symptoms or shared developmental stage as was the case with the DSM-IV-TR . Historically, disorders w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 76 publications
0
7
0
Order By: Relevance
“…Consistent with the maturational lag hypothesis, the oscillatory activity in children with ADHD looks like that of younger children. Consistent with the maturational deviance hypothesis, there is a characteristic topographical distribution of the oscillatory activity regardless of age (Burke and Edge, 2013). Overall, there are increased relative and/or absolute delta and theta activities (slow activity) specifically in the frontal and midline sites (for a review, see Barry et al, 2004;Mann et al, 1992).…”
Section: Discussionmentioning
confidence: 58%
“…Consistent with the maturational lag hypothesis, the oscillatory activity in children with ADHD looks like that of younger children. Consistent with the maturational deviance hypothesis, there is a characteristic topographical distribution of the oscillatory activity regardless of age (Burke and Edge, 2013). Overall, there are increased relative and/or absolute delta and theta activities (slow activity) specifically in the frontal and midline sites (for a review, see Barry et al, 2004;Mann et al, 1992).…”
Section: Discussionmentioning
confidence: 58%
“…In addition to alcoholics, enhanced tonic theta power has been observed in a variety of neurological disorders including Alzheimer's disease (Dauwels et al, 2010 ), vascular dementia (Babiloni et al, 2004 ), or attention deficit hyperactivity disorder (Burke and Edge, 2013 ). Likewise, increases in the tonic theta band have been remarked in altered neurophysiological states of the brain such as, drowsy and sleep states (Makeig et al, 2000 ; Tanaka et al, 2000 ) and after consumption of anesthetic drugs (Voss and Sleigh, 2007 ) or depressant substances such as, alcohol (Stenberg et al, 1994 ; Ehlers et al, 1998 ; Ilan and Gevins, 2001 ), which appears to suggest that when the ability to respond to external stimuli decreases, spontaneous theta activity increases (Klimesch, 1999 ).…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, and somewhat different from the conclusions of previous studies, instead of theta power, delta relative power had a profound effect on group differentiation. Some studies have proposed that an increase in the power of the delta band reflects the maturation lag of the brain in children with ADHD [55], [63], [64]. A longitudinal neuroanatomic study revealed that the cortical maturation trajectory in children with ADHD is approximately 3 years behind that of children with TD [65].…”
Section: Discussionmentioning
confidence: 99%
“…A longitudinal neuroanatomic study revealed that the cortical maturation trajectory in children with ADHD is approximately 3 years behind that of children with TD [65]. From an electrophysiological perspective, an increase in slow-wave activity (delta and theta) and a decrease in fast-wave activity (alpha and beta) are reminiscent of normal, but immature, cortical activity patterns that are frequently observed in younger children with TD [63], [64]. Based on the aforementioned facts, researchers have suggested that the increased slow-wave activity in children and adolescents with ADHD in the resting condition is associated with a maturational lag [55], [63].…”
Section: Discussionmentioning
confidence: 99%